Pelatihan Sepeda Motor Full Injeksi Untuk Mendukung Kompetensi Berwirausaha Pemuda Karang Taruna - Ahmad Kurniawan; Dedi Harianto; Mohamad Ikbal Riski A. Danial; Buya Hamka (PT. Global Research Collaboration, 2024)
Karang Taruna youth is an important asset in community and economic development at the local level. In this digital era, understanding and expertise in the field of technology is becoming increasingly important, including in the automotive sector. Full injection motorbike training is a relevant strategy in increasing entrepreneurial competence among Karang Taruna youth. This training aims to provide in-depth knowledge of the fuel injection system on motorbikes as well as practical skills in maintenance and repair. The full injection motorbike training method is divided into three stages, namely, entrepreneurship training, periodic service training stages and periodic service simulations. This training also provides opportunities and opportunities for training participants to start entrepreneurship, by facilitating the development of business plans that are oriented to the local market.